Recognition of sustainable packaging by consumers of household chemicals - Paták, Michal; Branská, Lenka; Hvězdová, Gabriela (My University, 2024)
The growing interest of companies in sustainability affects various areas of logistic activities, including packaging. There is a clear tendency among industrial companies to enhance the sustainability of packaging for their products. In doing so, companies contribute not only to the environmental behaviour of society but also to its overall well-being. However, for ultimate success in both business and society, it is important that consumers can recognise and appreciate these packaging efforts. The paper addresses the challenge of identifying sustainable packaging from the perspective of consumers, particularly in relation to the purchase of household chemicals such as detergents and cosmetics. Based on the literature review and focus group discussion, the paper reveals packaging indicators that enable consumers to identify sustainable packaging. A subsequent questionnaire survey involving 400 Czech consumers defines the relative importance of these indicators. Through exploratory factor analysis, the paper identifies six main factors in recognising sustainable packaging, namely graphic design, amount of material, type of material, brand, labelling, and reusability. Furthermore, the paper reveals differences in the perception of sustainable packaging based on the socio-demographic characteristics of consumers. Reusability, type of material, and labelling emerge as the most significant factors in packaging recognition within the Czech consumer market for household chemicals. While the impact of labelling and type of material factors varies depending on the education, age, and environmental inclination of consumers, the reusability factor equally influences all Czech consumers, regardless of gender, age, education, or lifestyle.
Rozpoznávání udržitelného zákazníky spotřební chemie
Keywords: sustainability; sustainable packaging; sustainable packaging indicator; consumer recognition; household chemicals; udržitelnost; udržitelný obal; indikátory udržitelného obalu; spotřebitelské rozpoznávání; spotřební chemie